2016
DOI: 10.1128/aac.02931-15
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Potential of Antifungal Drugs on ATP-Binding Cassette Transporters P-Glycoprotein, MRP1 to MRP5, BCRP, and BSEP

Abstract: dInhibition of ABC transporters is a common mechanism underlying drug-drug interactions (DDIs). We determined the inhibitory potential of antifungal drugs currently used for invasive fungal infections on ABC transporters P-glycoprotein (P-gp), MRP1 to MRP5, BCRP, and BSEP in vitro. Membrane vesicles isolated from transporter-overexpressing HEK 293 cells were used to investigate the inhibitory potential of antifungal drugs (250 M) on transport of model substrates. Concentration-inhibition curves were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 33 publications
2
74
0
3
Order By: Relevance
“…Fluconazole is a strong inhibitor of CYP2C19, a moderate CYP3A4 and CYP2C9 inhibitor . It is not an inhibitor but a substrate of P‐gp . Thus, DDI between fluconazole and tacrolimus is unlikely to involve P‐gp.…”
Section: Resultsmentioning
confidence: 99%
“…Fluconazole is a strong inhibitor of CYP2C19, a moderate CYP3A4 and CYP2C9 inhibitor . It is not an inhibitor but a substrate of P‐gp . Thus, DDI between fluconazole and tacrolimus is unlikely to involve P‐gp.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies indicated that M1‐1, M1‐2, and M1‐6 are CYP3A4, P‐gp, and BCRP substrates. Itraconazole is an inhibitor of CYP3A, P‐gp, and BCRP . Itraconazole may also have inhibited the metabolism and excretion of M1‐1, M1‐2, and M1‐6, thereby increasing their exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole has a high potential for drug interactions, as it inhibits CYP3A4, P-glycoprotein (P-gp), breast cancer resistance protein (BCRP) and bile salt export pump (BSEP) (Table 2) [113,114]. Itraconazole is also a substrate for P-gp and highly metabolized by CYP3A4, producing hydroxyl-itraconazole, keto-itraconazole and N-desalkyl-itraconazole [115].…”
Section: Busulfan Drug-drug Interactionsmentioning
confidence: 99%